Influence of barium titanate content and particle size on electromechanical coupling coefficient of lead-free piezoelectric ceramic-Portland cement composites - Rattiyakorn Rianyoi (2018)
The 0-3 lead-free piezoelectric ceramic-Portland cement composites were prepared by mixing and pressing the Portland cement (PC) and barium titanate (BT) ceramic powder. The influences of BT particle size and BT content on the electromechanical coupling coefficient (Kt) of the composites were investigated. The results indicate that the particle size of BT used to produce the composite under the conditions of the same BT content (at 50% BT) and fabrication technique has an influence on the Ktvalues. The electromechanical coupling coefficient was found to increase with the particle size of BT used where the values of Ktare found to be at 10.8% and 14.1% for composites with median particle size of 75 μm and 425 μm, respectively. Furthermore, Ktof composites increase with increasing content of BT (at the same particle size of 425 μm) when the content of BT reaches 70%, Ktis 16.6%. In addition, the acoustic impedance of the composite also increase with an increase of BT content. © 2012 Elsevier Ltd and Techna Group S.r.l.